Reassessing Bassam Tibi’s critique of the Islamic purification movement: A hadith and Salafi tradition perspective - Hadi, Sofyan; Sori, Sofian; Iskandar, Amin (UIN Sunan Gunung Djati Bandung, 2025)
This article critically examines Bassam Tibi's conception of contemporary Islamic purification movements in his work